A preliminary investigation of the relationship of dental fear to other specific fears, general fearfulness, disgust sensitivity and harm sensitivity - Armfield JM (Blackwell Synergy, 2008)
People with dental fear often suffer from other psychological disorders, as well as from a number of other specific fears